On Ecological Philosophy in Walden - Lu, Jie; Zhang, Zhiqiang (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Walden is the representative work of Henry David Thoreau, the most influential transcendentalist writer in the United States in the 19th century. The paper discusses the relationship between man and nature from the perspectives of ecological philosophy, anti-anthropocentrism and the inner spiritual ecological connotation of man. It points out that nature can endow people with the elements of inner beauty, and her unspeakable purity and kindness always endow people with health and joy; human beings, like other animals and plants, are part of the biosphere of nature; human happiness, freedom and civilization do not necessarily depend on the abundance of material life, but, to some extent, on the harmonious coexistence with nature.